Sustained Swimming Training Enhances Growth and Swimming Performance in Juvenile Coho Salmon (Oncorhynchus kisutch) with Limited Effects on Osmoregulatory-Related Traits - Wenda Cui; Hexiang Yang; Shuang Song; Linlin Dai; Hongyang Chen; Junjie Bai; Binbin Xing; Xintong Qiu (Fishes, 2026)
To evaluate the effects of swimming training on growth, swimming performance, and osmoregulatory-related indices in juvenile coho salmon, freshwater-reared fish were subjected to current of 1 body length per second (BL·s−1) from December 2024 to April 2025. Fork length, body weight, condition factor, insulin-like growth factor-1 (IGF-1), and gill and intestinal Na+/K+-ATPase (NKA) protein abundance were measured monthly, and critical swimming speed (Ucrit) was evaluated after one month of training. Trained fish showed greater fork length in March and higher body weight in March and April than controls. The condition factor was higher in trained fish in February and March, but declined during spring smolt development. Swimming capacity was enhanced by training, as indicated by significantly higher Ucrit. Mean IGF-1 levels did not differ between groups, but IGF-1 correlated positively with body size only in trained fish. No significant training effect was detected for either gill or intestinal NKA protein abundance, although gill NKA increased significantly in April, likely reflecting seasonal smoltification. In addition, IGF-1 was significantly correlated with gill NKA in trained fish in March. Collectively, these results indicate that sustained swimming training improves growth and swimming performance and may enhance associations among measured physiological variables during smoltification in juvenile coho salmon.